Faultlines : Writings on conflict & resolution (Vol.8) - Gill, K. P. S.(Ed.); Sahni,Ajai (Ed.) (New Delhi, 2001)
Terrorists combine extreme violence with a wide range of overground political activity by front organisations - public demonstrations, the adroit manipulation of the Press and the judicial process, and complex linkages with political parties, 'human rights' groups and 'legitimate' businesses. This volume explores the unique problems a democracy has in dealing with the collusive patterns through which terrorists exploit the institutional structures and freedoms of the very system they set out to destroy.
Keywords: Social conflict